A multi-scale synergistic pt-based single-atom reversible hydrogen fuel cell catalyst and a preparation method thereof
Patent Information
- Application Number
- CN202311595062.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-27
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2043-11-27
AI Technical Summary
然而,平面晶格配位原子微环境造成的单原子的高配位数和大电子损失率将导致金属原子暴露比低和H*-H2转化动力学缓慢,这不利于HER过程
[0018]1、本发明提供了一种多尺度协同的Pt基单原子可逆氢燃料电池催化剂及其制备方法,制备工艺简单。
Smart Images

Figure CN117673375B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrocatalyst technology, and in particular to a multi-scale synergistic Pt-based single-atom reversible hydrogen fuel cell catalyst and its preparation method. Background Technology
[0002] With societal development, human demand for energy is constantly increasing, especially in modern industrialization and urbanization, where dependence on energy is even more pronounced. However, the depletion of traditional energy sources and growing public concern about environmental issues have made hydrogen (H2) an ideal energy carrier to replace fossil fuels. Proton exchange membrane fuel cells (FEMFCs) are highly competitive in the transportation sector due to their advantages of power generation and zero carbon emissions. To promote their commercialization, it is necessary to improve fuel cell efficiency while reducing costs by preparing highly active and stable catalyst materials. The hydrogen evolution reaction (HER) is the reverse reaction of the hydrogen oxidation reaction (HOR); therefore, reversible hydrogen fuel cells can be prepared by constructing bifunctional catalysts (HER / HOR). From safety and cost perspectives, electrocatalytic water splitting under alkaline conditions is more attractive. However, the typical multi-step catalytic process hinders the efficient execution of the cathode HER. Specifically, alkaline HER includes the following steps: H2O adsorption, H2O dissociation (Volmer step), and H desorption (Heyrovsky or Tafel step).
[0003] Pt-based single-atom catalysts (SACs) possess unique electronic structures and geometries. During catalytic reactions, single-atom catalytic sites can significantly improve atom utilization and mass exchange, thus accelerating the reaction rate. However, most current research on basic Pt-based single-atom catalysts only promotes one step in the basic HER process (Volmer step or Heyrovsky / Tafel step), and cannot simultaneously accelerate the entire HER process. Furthermore, metal single atoms are primarily anchored in the planar lattice of two-dimensional substrate materials, such as platinum atoms anchored in monolayer WO3 nanosheets (Pt). SA / ML-WO3) and NiO / Ni nanosheets (Pt SA -NiO / Ni). However, the high coordination number and large electron loss rate of single atoms caused by the microenvironment of coordinating atoms in the planar lattice will lead to a low metal atom exposure ratio and slow H*-H2 conversion kinetics, which is unfavorable to the HER process.
[0004] Therefore, designing Pt-based single-atom catalysts with multi-site synergy, reasonable coordination environment and electronic structure to accelerate the oxidation of H2 and the dissociation of H2O in alkaline media and the subsequent generation / release of H2 is an important research direction in this field. Summary of the Invention
[0005] The purpose of this invention is to provide a multi-scale synergistic Pt-based single-atom reversible hydrogen fuel cell catalyst and its preparation method. To achieve the above objective, the technical solution of this invention is as follows:
[0006] The first step is to prepare the electrodeposition precursor solution: a certain mass of cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and cobalt chloride hexahydrate (CoCl2·6H2O) are dissolved in deionized water, and chloroplatinic acid (H2PtCl6) is dispersed or dissolved in KOH solution. The corresponding precursor solutions are obtained by stirring or sonication.
[0007] The concentration of cobalt nitrate hexahydrate is 15-20 mM, preferably 17.2 mM; the concentration of cobalt chloride hexahydrate is 1.0-1.5 mM, preferably 1.1 mM; the concentration of chloroplatinic acid is 300-400 μM, preferably 318 μM; and the concentration of KOH solution is 0.2-1.0 M, preferably 0.5 M.
[0008] The second step is to prepare a Pt-based single-atom catalyst with a sea-island-like structure (LIS Pt). SA -Co-Co(OH)2):
[0009] (1) The fabric loaded with silver nanowires (Ag-NWs) was immersed in the Co(NO3)2·6H2O precursor solution prepared in the first step. Using Ag-NWs as a template, Pt sheet and saturated calomel electrode (SCE) were used as the relative electrode and reference electrode, respectively, and Co(OH)2 was obtained by electrochemical deposition.
[0010] Furthermore, the electrochemical deposition conditions were as follows: Co(OH)₂ was prepared by electrochemical deposition for 200s-800s, preferably 500s, using a chronoamperometry method on an electrochemical workstation at a voltage of -1.2 to -0.8V, preferably -1.0V; the synthesized Co(OH)₂ was then immersed in 1 M KOH solution and subjected to linear sweep voltammetry (LSV) tests at -0.9 to -1.3V to stabilize its structure.
[0011] (2) The Co(OH)2 prepared in step (1) was immersed in the CoCl2·6H2O precursor solution, and the Pt sheet and saturated calomel electrode (SCE) were used as the counter electrode and the reference electrode, respectively, and LIS Co-Co(OH)2 was obtained by electrochemical deposition.
[0012] Furthermore, the electrochemical deposition conditions were as follows: LIS Co-Co(OH)2 was obtained by deposition at a potential of -1.5 to -1.0 V, preferably -1.2 V, using chronoamperometry for 100 s to 500 s, preferably 200 s; the synthesized LIS Co-Co(OH)2 was then immersed in 1 M KOH solution and subjected to LSV testing at -0.9 to -1.3 V to stabilize its structure.
[0013] (3) LIS Co-Co(OH)2 was immersed in an aqueous solution of H2PtCl6, with Pt sheet and Hg / HgO electrode serving as counter and reference electrodes, respectively, and LIS Pt was obtained by electrochemical deposition. SA -Co-Co(OH)2.
[0014] Furthermore, the electrochemical process was conducted using cyclic voltammetry, with a potential range of -0.92 to -1.4 V and a scan rate of 5 mV / s. -1 Repeat 5-30 times, preferably 10 times.
[0015] The obtained catalyst is LIS Pt SA -Co-Co(OH)2 nanomaterials loaded onto Ag NWs; the LIS Pt SA -Co-Co(OH)2: The Co(OH)2 nanosheets supporting the metallic Co have an island-like layered nanostructure. Metallic Co nanoislands are constructed on Co(OH)2, and Pt single atoms are anchored at the edges of the metallic Co nanoislands.
[0016] The catalyst obtained by this invention can be used to generate H2 from dissociated water in an alkaline medium, and a high current density can be obtained at a low overpotential.
[0017] The advantages of this invention are:
[0018] 1. This invention provides a multi-scale synergistic Pt-based single-atom reversible hydrogen fuel cell catalyst and its preparation method, which is simple to prepare.
[0019] 2. This catalyst can simultaneously satisfy HER / HOR under alkaline electrolyte conditions. This fuel cell can be charged and discharged. The catalyst can satisfy both HER and HOR functions and can be combined with OER / ORR bifunctional catalysts to assemble a reversible hydrogen fuel cell. When charging, the HER reaction occurs, and when discharging, the HOR reaction occurs.
[0020] 3. By designing Pt-based single-atom catalysts with multi-site synergy, reasonable coordination environment and electronic structure, the oxidation of H2 and the dissociation of H2O in alkaline media and the subsequent generation / release of H2 can be accelerated. Attached image description:
[0021] Figure 1 Embodiment 1 of the present invention is based on LIS Pt SA XRD characterization of the -Co-Co(OH)2 catalyst.
[0022] Figure 2 Embodiment 1 of the present invention is based on LIS Pt SA Morphology characterization diagram of the -Co-Co(OH)2 catalyst.
[0023] Figure 3 Embodiment 1 of the present invention is based on LIS Pt SA Comparison of hydrogen evolution performance of -Co-Co(OH)2 catalyst. Detailed Implementation
[0024] The present invention will be further described below with reference to the embodiments, but the present invention is not limited to the following embodiments.
[0025] Example 1
[0026] A multi-scale synergistic Pt-based single-atom reversible hydrogen fuel cell catalyst (LIS Pt) SA The following is a description of Co-Co(OH)₂ and its preparation method:
[0027] Step 1: Preparation of Co(OH)₂: Fabric loaded with Ag-NWs was immersed in a 17.2 mM Co(NO₃)₂·6H₂O aqueous solution. Using Ag-NWs as a template, a Pt sheet and a saturated calomel electrode (SCE) were used as the counter and reference electrodes, respectively. Co(OH)₂ was electrochemically deposited at -1.0 V for 500 s using a chronoamperometry method on an electrochemical workstation. The synthesized Co(OH)₂ was then immersed in a 1 M KOH solution and subjected to linear sweep voltammetry (LSV) tests at -0.9 to -1.3 V to stabilize its structure. Subsequently, the Co(OH)₂ was washed with ethanol and deionized water and dried in air for later use.
[0028] The second step involved the preparation of LIS Co-Co(OH)₂: Co(OH)₂ was immersed in a 1.1 mM aqueous solution of CoCl₂·6H₂O, with a Pt sheet and a saturated calomel electrode (SCE) serving as the counter and reference electrodes, respectively. LIS Co-Co(OH)₂ was obtained by chronoamperometry deposition for 200 s at a potential of -1.2 V. Similarly, the synthesized LIS Co-Co(OH)₂ was immersed in a 1 M KOH solution, and LSV testing was performed at -0.9 to -1.3 V to stabilize its structure.
[0029] The third step is to prepare LIS Pt. SA -Co-Co(OH)2: LIS Pt was prepared by electrochemical deposition in a 0.5M KOH solution containing 318μM H2PtCl6, using a Pt sheet and an Hg / HgO reference electrode as the counter and reference electrodes, respectively. SA -Co-Co(OH)₂ catalyst. The electrochemical process was conducted using cyclic voltammetry, with a potential range of -0.92 to -1.4 V and a scan rate of 5 mV / s. -1 The process was repeated 10 times. After deposition, LIS Pt was washed with ethanol and deionized water. SA -Co-Co(OH)2 electrode.
[0030] Example 2
[0031] Pt SA Preparation method of -Co(OH)2 catalyst:
[0032] Step 1: Preparation of Co(OH)₂: Fabric loaded with Ag-NWs was immersed in a 17.2 mM Co(NO₃)₂·6H₂O aqueous solution. Using Ag-NWs as a template, a Pt sheet and a saturated calomel electrode (SCE) were used as the counter and reference electrodes, respectively. Co(OH)₂ was electrochemically deposited at -1.0 V for 500 s using a chronoamperometry method on an electrochemical workstation. The synthesized Co(OH)₂ was then immersed in a 1 M KOH solution and subjected to LSV testing at -0.9 to -1.3 V to stabilize its structure. Subsequently, the Co(OH)₂ was washed with ethanol and deionized water and dried in air for later use.
[0033] The second step is to prepare Pt. SA -Co(OH)2: Pt was prepared by electrochemical deposition in a 0.5M KOH solution containing 318μM H2PtCl6, using a Pt sheet and an Hg / HgO reference electrode as the counter and reference electrodes, respectively. SA -Co(OH)₂ catalyst. The electrochemical process was conducted using cyclic voltammetry, with a potential range of -0.92 to -1.4 V and a scan rate of 5 mV / s. -1 The process was repeated 10 times. After deposition, the Pt was washed with ethanol and deionized water. SA -Co(OH)2 electrode.
[0034] Example 3
[0035] Pt SA -Preparation method of Co catalyst:
[0036] Step 1: Preparation of Co: Fabric loaded with Ag-NWs was immersed in a 1.1 mM CoCl₂·6H₂O aqueous solution. A Pt sheet and a saturated calomel electrode (SCE) were used as the counter and reference electrodes, respectively. Co was deposited by chronoamperometry for 200 s at a potential of -1.2 V. The synthesized Co was then immersed in a 1 M KOH solution and subjected to LSV testing at -0.9 to -1.3 V to stabilize its structure. Subsequently, the Co was washed with ethanol and deionized water and dried in air for later use.
[0037] The third step is to prepare Pt. SA -Co: Pt was prepared by electrochemical deposition in a 0.5M KOH solution containing 318μM H2PtCl6, using a Pt sheet and an Hg / HgO reference electrode as the counter and reference electrodes, respectively. SA-Co catalyst. The electrochemical process was performed using cyclic voltammetry, with a potential range of -0.92 to -1.4 V and a scan rate of 5 mV / s. -1 The process was repeated 10 times. After deposition, the Pt was washed with ethanol and deionized water. SA -Co electrode.
[0038] Example 4
[0039] Preparation method of Pt / C electrode:
[0040] The first step is to disperse 5.0 mg Pt / C (20 wt%) in 0.98 mL of ethanol containing 0.02 mL Nafion (5 wt%) to form a dispersion ink;
[0041] The second step involves depositing dispersed Pt / C ink onto a carbon paper substrate to prepare an area loading of 1.00 mg / cm². -2 Pt / C electrode.
[0042] Select the LIS Pt prepared in Example 1 above. SA The -Co-Co(OH)2 catalyst was characterized by XRD and morphology, and its electrochemical performance was tested:
[0043] 1. LIS Pt SA XRD characterization of the -Co-Co(OH)2 catalyst:
[0044] LIS Pt prepared in this invention SA XRD pattern of -Co-Co(OH)2 catalyst Figure 1 As shown, due to the low concentration of the precursor solution for Co preparation, X-ray diffraction (XRD) results were observed. Figure 1 No characteristic peaks of Co and Pt were detected in LIS Pt. SA -Co-Co(OH)₂ contains no Pt clusters or particles. To further verify the synthesis method of metallic Co, the concentration of the Co precursor solution was increased by two times, and conductive fluorine-doped tin oxide (FTO) glass was selected as the substrate to prepare metallic Co thin films. Figure 1 As shown in Figure b, metallic Co was detected by XRD pattern, confirming that the above method successfully prepared metallic Co on Co(OH)2 nanosheets.
[0045] 2. LIS Pt SA Morphology and structural characterization of the -Co-Co(OH)2 catalyst:
[0046] like Figure 2 As shown in Figure a, LIS Pt is deposited using a three-step electrochemical deposition method. SA-Co-Co(OH)₂ nanomaterials were loaded onto Ag NWs. High-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) was used. Figure 2 Image b) shows that the Co(OH)₂ nanosheets supporting metallic Co exhibit an island-like, layered nanostructure, with bright spots corresponding to dispersed single-atom Pt. These results demonstrate the successful construction of metallic Co nanoislands on Co(OH)₂, with Pt single atoms anchored at the edges of the metallic Co nanoislands without altering the phase structure of Co and Co(OH)₂.
[0047] 3.LIS Pt SA Hydrogen evolution performance test of -Co-Co(OH)2 catalyst:
[0048] Using an Hg / HgO electrode assembly as the reference electrode and a Pt sheet as the counter electrode, LISPt was grown in situ on silver nanowires. SA -Co-Co(OH)2 is used as the working electrode, and a three-electrode electrochemical system is formed with an alkaline aqueous solution (preferably 1M potassium hydroxide solution) to produce hydrogen by electrolysis of water; more preferably, a voltage of 0 to -0.35V is used; the scanning direction is from 0 to -0.35V.
[0049] The performance remains basically unchanged after 40 hours of continuous operation.
[0050] The HER activity of the sample in 1M KOH solution was evaluated by electrochemical measurements, and the optimal catalytic performance was obtained by optimizing the electrochemical synthesis parameters. Figure 3 As shown, LIS Pt SA -Co-Co(OH)2 exhibits the best HER performance among all catalysts, requiring only a low overpotential of 97 mV to achieve a 100 mA cm⁻¹. -2 High current density.
[0051] Under alkaline conditions, the synergistic effect of the Co-Co(OH)₂ interface exhibits strong H₂O adsorption and dissociation capabilities, effectively promoting the Volmer step of HER in alkaline solution. Furthermore, the non-coordination defect sites at the edges of the Co nanoislands provide abundant sites for anchoring Pt single atoms. Pt atoms anchored at the metal edges show a larger atomic exposure ratio and metalloid electronic states, enabling Pt atoms to simultaneously bind multiple H atoms, promoting the H*-H₂ conversion under alkaline conditions, and thus simultaneously facilitating the multi-step reaction for hydrogen production via water electrolysis under alkaline conditions.
Claims
1. A method for preparing a multi-scale synergistic Pt-based single-atom reversible hydrogen fuel cell catalyst, characterized in that, Includes the following steps: The first step is to prepare the electrodeposition precursor solution: a certain mass of cobalt nitrate hexahydrate (Co(NO3)2•6H2O) and cobalt chloride hexahydrate (CoCl2•6H2O) are dissolved in deionized water, and chloroplatinic acid (H2PtCl6) is dispersed or dissolved in KOH solution. The corresponding precursor solutions are obtained by stirring or sonication. The second step is to prepare a Pt-based single-atom catalyst with a sea-island-like structure (LIS Pt). SA -Co-Co(OH)2): (1) The fabric loaded with silver nanowires (Ag-NWs) was immersed in the Co(NO3)2•6H2O precursor solution prepared in the first step. Using Ag-NWs as a template, Pt sheet and saturated calomel electrode (SCE) were used as the relative electrode and reference electrode, respectively, and Co(OH)2 was obtained by electrochemical deposition. (2) The Co(OH)2 prepared in step (1) was immersed in the CoCl2•6H2O precursor solution, and the Pt sheet and saturated calomel electrode (SCE) were used as the counter electrode and the reference electrode, respectively, and LIS Co-Co(OH)2 was obtained by electrochemical deposition. (3) LIS Co-Co(OH)2 was immersed in an H2PtCl6 precursor solution, with Pt sheet and Hg / HgO electrode serving as counter and reference electrodes, respectively, and LIS Pt was obtained by electrochemical deposition. SA -Co-Co(OH)2; The catalyst is used to generate H2 from dissociated water in an alkaline medium, achieving a high current density at a low overpotential.
2. The method according to claim 1, characterized in that, In the first step, the concentration of cobalt nitrate hexahydrate is 15-20 mM, the concentration of cobalt chloride hexahydrate is 1.0-1.5 mM, the concentration of chloroplatinic acid is 300-400 μM, and the concentration of KOH solution is 0.2-1.0 M.
3. The method according to claim 2, characterized in that, The concentrations of cobalt nitrate hexahydrate and cobalt chloride hexahydrate were 17.2 mM, 1.1 mM, 318 μM, and 0.5 M, respectively.
4. The method according to claim 1, characterized in that, The conditions for electrochemical deposition in step (1) are as follows: Co(OH)2 is prepared by electrochemical deposition for 200s-800s at -1.2~-0.8 V using the chronoamperometry method of an electrochemical workstation; the synthesized Co(OH)2 is immersed in 1 M KOH solution and subjected to linear sweep voltammetry (LSV) test at -0.9~-1.3 V to stabilize its structure.
5. The method according to claim 4, characterized in that, Co(OH)₂ was prepared by electrochemical deposition for 500 s at -1.0 V using a chronoamperometry method on an electrochemical workstation.
6. The method according to claim 1, characterized in that, In step (2), the electrochemical deposition conditions were as follows: LIS Co-Co(OH)2 was obtained by deposition for 100s-500s using the chronoamperometry method at a potential of -1.5~-1.0V. The synthesized LIS Co-Co(OH)2 was immersed in 1 M KOH solution and LSV test was performed at -0.9~-1.3 V to stabilize its structure.
7. The method according to claim 6, characterized in that, In step (2), the electrochemical deposition conditions were as follows: LIS Co-Co(OH)2 was obtained by deposition for 200 s using the chronoamperometry method at a potential of -1.2 V.
8. The method according to claim 1, characterized in that, In step (2), the electrochemical process is carried out by cyclic voltammetry, with a potential range of -0.92 ~ -1.4 V and a scan rate of 5 mV s. -1 Repeat 5-30 times.
9. The method according to claim 8, characterized in that, Repeat 10 times.
10. A multi-scale synergistic Pt-based single-atom reversible hydrogen fuel cell catalyst prepared according to any one of claims 1-9, wherein the obtained catalyst is LIS Pt. SA -Co-Co(OH)₂ nanomaterials are loaded onto Ag NWs; the LISPt SA -Co-Co(OH)2: The Co(OH)2 nanosheets supporting metallic Co have an island-like layered nanostructure. Metallic Co nanoislands are constructed on Co(OH)2, and Pt single atoms are anchored at the edges of the metallic Co nanoislands.
11. The application of the multi-scale synergistic Pt-based single-atom reversible hydrogen fuel cell catalyst prepared according to any one of claims 1-9 for hydrogen production from water dissociation in an alkaline medium.
12. The application according to claim 11, achieving 100 mA cm⁻¹ at a low overpotential of 97 mV. -2 High current density.
Citation Information
Patent Citations
Visual electro-catalytic material as well as preparation method and application thereof
CN114892211A
Preparation method of Pt-NiP / Co (OH) 2 composite material for electro-catalytic hydrogen production
CN116463671A